A Review of Corporate Social Responsibility (CSR) Programs for Community-Based Sustainable Development in Indonesia - Edison Hatoguan Manurung; Aaraf Sharma; Rohan Kumar (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. Corporate Social Responsibility (CSR) programs play a vital role in promoting community-based sustainable development, particularly in developing countries like Indonesia. As industries expand, the need for companies to engage in socially responsible practices has become increasingly important to address environmental, social, and economic challenges. Purpose. This study aims to review CSR programs implemented by companies in Indonesia and assess their impact on community-based sustainable development. The research explores various CSR initiatives, focusing on their alignment with the Sustainable Development Goals (SDGs) and their contributions to local communities. Method. A comprehensive literature review and case study analysis were employed as the research methodology. Data was collected from academic articles, CSR reports, and case studies of companies that have implemented community-driven CSR programs in Indonesia. The study evaluates the types of CSR activities, the sectors involved, and the outcomes for community development. Results. The findings indicate that CSR programs in Indonesia have led to significant improvements in education, healthcare, and environmental sustainability in local communities. However, challenges such as limited stakeholder engagement, insufficient long-term planning, and a lack of monitoring mechanisms hinder the effectiveness of some initiatives. The study also reveals that successful CSR programs are those that actively involve local communities in decision-making and are aligned with their needs. Conclusion. In conclusion, CSR programs in Indonesia have the potential to contribute to sustainable community development, but they require stronger alignment with local priorities, better long-term strategies, and enhanced monitoring to maximize their impact.